A novel fuzzy reset method for pressure control of proton exchange membrane fuel cell in the presence of uncertainty. (27th September 2021) - Linli, Wu; Fatemi Golshan, Mehrdad
Summary: Proton exchange membrane fuel cell as one of the most progressive and extensively used kinds of fuel cells has an effect character in the creation of renewable energy, and control of its principal modules, including the supply manifold, is one of the objectives of recent research. This study suggests a novel robust structure to regulate the supply manifold pressure at the cathode side in addition to cover the nonlinear behavior of fuel cells and achieve optimal performance. Therefore, this article studies a delayed transfer function model that, in addition to considering the effects of uncertainty and the nonlinear behavior of the supply manifold, has the simplicity necessary for designing an operational control method. The proposed control method also consists of two main parts: One is the reset control method, which is designed to improve the transient response in adjusting the supply manifold pressure, and the other is the fuzzy part, which is planned to tune the reset control method coefficients. The simulation and comparison results show the capabilities of the proposed hybrid method to improve the transient response of the system from different perspectives and stability despite the effects of uncertainty.